What in God's name are you eating? how can Christians live and eat responsibly in today's global village? - Francis, Andrew, 1956- (Cambridge : Lutterworth Press, 2015)
How you eat affects the planet-and everyone else on it. What you eat might literally cost the earth. But it also has implications for your health, the grower or producer, and the way you think about the world. 'What in God's Name Are You Eating?' is full of questions and information to help you and those you live and work with reflect on major issues about food and lifestyle.Andrew Francis is a community theologian who grows vegetables and fruit in his backyard, bakes bread, and cooks for family, friends, coworkers, and his students. He is an artist and poet who puts his hands in the earth, wh.
13: Developing a Global Strategy14: Conclusions; Bibliography; Back cover
Description based on CIP data; item not viewed.
Master record variable field(s) change: 072
Keywords: Food -- Religious aspects -- Christianity; Food -- Moral and ethical aspects; Food industry and trade -- Moral and ethical aspects; Food industry and trade -- Moral and ethical aspects; Food -- Moral and ethical aspects; Food -- Religious aspects -- Christianity; COOKING / General; RELIGION / Christian Theology / Ethics; Food -- Religious aspects -- Christianity; Human ecology -- Religious aspects -- Christianity; Sustainable agriculture; RELIGION / Christian Life / Social Issues; Electronic books